2000
DOI: 10.1016/s0304-3959(99)00294-8
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of cholecystokinin octapeptide and angiotensin II in reversal of morphine induced analgesia in rats

Abstract: The aim of this paper is to study the synergistic anti-analgesic effect of angiotensin II (Ang II) plus cholecystokinin octapeptide (CCK-8). Our previous studies have shown that both CCK-8 and Ang II are potent anti-opioid substances. Intracerebroventricular (i.c.v.) injection of CCK-8 or Ang II dose-dependently antagonizes morphine-induced analgesia (MIA). In the present study, we observed the combined effect of CCK-8 and Ang II in antagonizing MIA. CCK-8 and Ang II were injected intracerebroventricularly to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Synergism between ZOL and paclitaxel/cisplatin was evaluated by isobolographic analysis[24]. This method is referred to as a ‘gold standard’ because it is the only model of analysis proven valid for analyzing interactions between biologically active agents [24][28].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Synergism between ZOL and paclitaxel/cisplatin was evaluated by isobolographic analysis[24]. This method is referred to as a ‘gold standard’ because it is the only model of analysis proven valid for analyzing interactions between biologically active agents [24][28].…”
Section: Methodsmentioning
confidence: 99%
“…This method is referred to as a ‘gold standard’ because it is the only model of analysis proven valid for analyzing interactions between biologically active agents [24][28]. Briefly, doses of ZOL were plotted on the x -axis and doses of paclitaxel/cisplatin were plotted on the y -axis, and points representing equal effects on cell viability were connected to obtain an isobologram.…”
Section: Methodsmentioning
confidence: 99%
“…However, another possible explanation for the increased expression of AT1 receptor mRNA relates to immunohistochemical observations showing that the AT1 receptor is found in axonal fibers and terminals in lamina II of the dorsal horn (Ahmad et al, 2003). Lamina II is the site of termination for nociceptive fibers and there is precedence for a role of angiotensin II in modulating pain pathways-centrally administered angiotensin II attenuates morphineinduced analgesia in mice and rats (Han et al, 2000;Kaneko et al, 1985). Moreover, studies that have examined whether endogenous opioids are operative in modulating the CNS action of angiotensin II (ang II) on blood pressure have shown that endogenous opioids modulate the pressor response to intracerebral ang II and that this effect is mediated mainly through endogenous kappa opioid receptors (Rabkin, 2007).…”
Section: Decreased Opioid Receptor Expressionmentioning
confidence: 99%
“…A variety of other receptors, enzymes and cytokines that play a role in the modulation of pain and inflammation have been identified and are being researched as potential targets for novel analgesics. These include, but are not limited to, angiotensin II, glycine, glutamate, GABA and protein kinase [155,[457][458][459][460][461][462][463][464][465][466][467][468][469][470][471][472][473][474]. A detailed discussion of this literature to date is beyond the scope of this review.…”
Section: Other Potential Targetsmentioning
confidence: 99%